Classification of Diabetic Retinopathy Disease Levels by Extracting Topological Features Using Graph Neural Networks - Pondugula Divya; Dr. K V V SATYANARAYANA (Utilitas Mathematica, 2025)
Diabetic retinopathy (DR) is one of the most common causes of blindness in the world”. It has to be diagnosed quickly and accurately so that treatment may begin as soon as possible. Manual examination of fundus photographs by doctors is prone to mistakes and is labor-intensive. “Using computer-assisted methods, especially Convolutional Neural Networks (CNNs), to automate DR diagnosis seems promising”.